2017
DOI: 10.1021/acs.cgd.7b00144
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Hygroscopicity of the Anti-Tuberculosis Drug (S,S)-Ethambutol Using Multicomponent Crystal Forms

Abstract: Ethambutol (ETB) is a chiral dibasic compound formulated and marketed as the (S,S)-ethambutol dihydrochloride, (S,S)-EDH, to treat tuberculosis. It is administered orally in a solid formulation composed of isoniazid, rifampicin, and pyrazinamide as a fixed-dose combination tablet. Because of its high hygroscopicity, (S,S)-EDH is known for catalyzing the degradation of isoniazid by rifampicin to yield isonicotinyl hydrazone. In order to avoid or even minimize these mutual drug–drug interactions, in this work we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…The developed salts had higher thermal stability than the free base without the presence of any phase transition. ETH-oxalate salts were observed to be non-hygroscopic, whereas the other three salts retained the hygroscopic nature of the free base …”
Section: Methodologies Of Salt Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed salts had higher thermal stability than the free base without the presence of any phase transition. ETH-oxalate salts were observed to be non-hygroscopic, whereas the other three salts retained the hygroscopic nature of the free base …”
Section: Methodologies Of Salt Preparationmentioning
confidence: 99%
“…ETH-oxalate salts were observed to be non-hygroscopic, whereas the other three salts retained the hygroscopic nature of the free base. 58 Recently, Cvetkovski et al, 2017, reported the formation of two new pharmaceutical salts of pyridoxine (PYR), prepared with syringic acid and ferulic acid via slow solvent evaporation, after dissolving the drug and salt formers in individual solvents or mixtures (1:1 stoichiometric ratio). Hirshfeld surface analysis was used to explore the intermolecular interactions between the API and the salt former and indicated the robustness of the pyridine/carboxylic acid as supramolecular synthons.…”
Section: Methodologies Of Salt Preparationmentioning
confidence: 99%
“…Several other salt forms (sulfate, dimesylate, ditosylate, dibesylate, and fumarate) have been prepared earlier but mostly were found to be hygroscopic . Diniz et al recently reported new multicomponent crystals of ethambutol obtained with a series of carboxylic/dicarboxylic acids, trichloroacetic, maleic, oxalic, and terephthalic acids . Among them, the oxalic acid salt showed relatively high stability (up to 48 h) toward hydration under humid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…29−31 Packing polymorphs include crystal systems having similar molecular conformations, differing only in the arrangement of molecules in their crystal packing environment. 32−34 The polymorphic forms of a drug may exhibit distinct solid-state physicochemical properties such as intrinsic dissolution rate, 35,36 solubility, 37 tabletability, 38,39 thermal stability, 40 flowability, 41 hygroscopicity, 42,43 etc. and also various drug outcomes such as drug efficacy, 44 bioavailability, 45 and toxicity.…”
Section: Introductionmentioning
confidence: 99%